Effects of a tailored strength training program of the upper limb combined with transcranial direct current stimulation (tDCS) in chronic stroke patients: study protocol for a randomised, double-blind, controlled trial - Marie-Hélène Milot; Stephania Palimeris; Hélène Corriveau; François Tremblay; Marie-Hélène Boudrias (BMC, 2019)
Abstract Background A significant proportion of individuals are left with poor residual functioning of the affected arm after a stroke. This has a great impact on the quality of life and the ability for stroke survivors to live independently. While strengthening exercises have been recommended to improve arm function, their benefits are generally far from optimal due to the lack of appropriate dosing in terms of intensity. One way to address this problem is to develop better tools that could predict an individual's potential for recovery and then adjust the intensity of exercise accordingly. In this study, we aim at determining whether an individualized strengthening program based on the integrity of the corticospinal tract, as reflected in the amplitude of motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS), in conjunction with transcranial direct current stimulation (tDCS), could lead to more optimal outcomes in terms of arm function in chronic stroke patients. Methods This multicentre, double-blinded, randomised controlled trial will aim to recruit 84 chronic stroke patients. Before and after training, participants will undergo a clinical evaluation, assessing motor recovery of the affected arm (Fugl-Meyer Stroke Assessment-FMA) and a TMS evaluation to assess the integrity of the corticospinal tract, as reflected in MEP amplitude. Based on their baseline MEPs amplitude, participants will be stratified into three groups of training intensity levels determined by the one-repetition maximum (1RM); 1) low: 35-50% 1 RM (MEPs < 50 μV); 2) moderate: 50-65% 1RM (MEPs 50-120 μV); and 3) high: 70-80% 1RM (MEPs > 120 μV). Training will target the affected arm (3 times/week for 4 weeks). In addition, participants will be randomly allocated into two tDCS groups (real vs. sham) and tDCS will be applied in an anodal montage during the exercise. Discussion This study will determine whether an individualized strength training intervention in chronic stroke survivors can lead to improved arm function. In addition, we will also determine whether combining anodal tDCS over the lesioned hemisphere with strength training can lead to further improvement in arm function, when compared to sham tDCS. Trial registration ClinicalTrials.gov Identifier: NCT02915185. Registered September 21 2016.